Selected Aspects of Foster Care Systems in Poland and Germany - Sophia Hoppe; Piotr Kulikowski; Friederike Lorenz-Sinai; Astrid MÄ™czkowska-Christiansen; Sylwester Zagulski (Social Work and Society)
This article compares the foster care systems in Poland and Germany, particularly focusing on the moment when young people are prepared to leave the support system and live an independent adult life. The data was collected as part of the work of an international project team in Poland and Germany in the framework of a joint research project, and included an analysis of foundational data (systematic textual analysis and secondary data analysis). An important part of the article is an analysis of the reforms of the foster care system in both countries. In Germany the reform was implemented in 2021 and in Poland the relevant law was changed in September 2022. The result is a comparison of the support systems Poland and Germany offer care leavers and a preliminary assessment of the reforms recently introduced in both countries.